ChemInform Abstract: Synthesis of Branched Carbasugars via Photooxygenation and Manganese(III) Acetate Free Radical Cyclization. Issue 51 (23rd December 2014) - Altun, Yasemin; Dogan, Sengul Dilem; Balci, Metin
Abstract Transformation of cyclohexadienes (I) and (IX) to carbasugars (VIII) and (XII), resp., is described.